Identifikasi dan Analisis Pengetahuan Mahasiswa Ilmu Keolahragaan Angkatan 2019 Terhadap Olahraga Tradisional Indonesia - Ferry Kusuma; Andun Sudijandoko (Indonesian Journal of Kinanthropology (IJOK), 2022)
Background: The purpose of this study was to determine the knowledge of the 2019 class of sports science students towards Indonesian traditional sports. Methods: This type of research uses quantitative descriptive, using survey methods and the way the data is collected the researchers use google form media to assist students in filling out questionnaires. Results: Students' knowledge of traditional Indonesian sports is in the high category. Conclusions: Based on the results of the research that has been carried out and the results of the discussion above, the following conclusions can be put forward: Students of Sports Science class 2019 against Indonesian traditional sports in the category of knowledge distribution: very high at 3%, high category at 38%, moderate category at 32 %, the low category is 15%, the very low category is 12%. Student of Sports Science class of 2019. In this study it can also be concluded that his understanding of traditional Indonesian sports is in the high category with a percentage of 38%. And very high at 3%.